Utilization of antiretroviral therapy services and associated factors among adolescents living with HIV in northern Uganda: A crosssectional study - Odongo, Innocent; Arim, Barbara; Ayer, Patrick; Murungi, Tom; Akullo, Susan; Aceng, Docus; Oboke, Henry; Kumakech, Edward; Obua, Celestino; Auma, Anna Grace; Nyeko, Richard (PLoS ONE, 2023)
Background: Suboptimal utilization of antiretroviral therapy (ART) services remains a problem among adolescents in low- and middle-income countries, which has a negative impact on them response to treatment and increases the risk of developing resistance. Optimal use is essential to enhancing treatment efficacy. We investigated the optimal use of ART service and predictors among adolescents living with HIV (ALHIV) in northern Uganda. Methods: We used a cross-sectional study design to collect quantitative data from 293 ALHIV at three health facilities in Lira municipality, northern Uganda. We used an interviewer administered questionnaire and data abstraction form. Data were analysed using SPSS version 23 software. Descriptive analysis and logistic regressions were performed to determine the relationship between the predictor and outcome variables. Statistical significance was determined at P-value<0.05 and the adjusted odds ratio with a 95% confidence interval was used. Results: The level of utilization of ART services was suboptimal among 27.6% (81/293) of the participants, and only 63.1% (185/293) were virally suppressed. Of the participants who were optimally utilizing ART services, the majority 86.8% (184/212) were virally suppressed. Age 10– 14 years (aOR = 3.34), the presence of both parents (aOR = 1.85), parental and peer reminders (aOR = 2.91) and (aOR = 0.49) respectively, and being on ART for five years or less were the characteristics related with optimal utilization of ART services Conclusions and recommendations: Not all ALHIV used ART services to their full potential. However, factors such as participants’ age, the presence of both parents, reminders from parents and peers, and being on ART for some time were all related to the optimal use of ART services. There is a need for developing strategies to increase family and peer support with a focus on older adolescents if the 95-95-95 goal is to be achieved in this age group.
Keywords: Antiretroviral therapy; HIV; Uganda; Treatment